Effect of Tuber Size and Intra-Row Spacing on the Yield and Quality of Potato (Solanum tuberosum L.) Varieties - Miressa Regasa; Weyessa Garedew; Ambecha Olika (Advances in Agriculture)
A field experiment was conducted at Nono Benja District from December 2013 to May 2014 under irrigation to assess the response of different sizes of seed tubers and intra-row spacing on the yield and quality of potato varieties. The treatments consisted of a factorial combination of two varieties (Jalenie and Gudenie): five levels of tuber size (20–35, 36–50, 51–65, 66–80, and 81–95 g) and five levels of intra-row spacing (20, 25, 30, 35, and 40 cm). The treatments were arranged in a split-split plot design (variety on main plot, intra-row spacing on subplot, and tuber size on sub-sub plot) with three replications. There were significant interaction effects of variety, intra-row spacing, and tuber size (P<0.05) on plant height, number of main stems per plant, average tuber weight, tuber number per plant, total tuber yield, marketable tuber yield, unmarketable tuber yield, large tuber mean yield, medium tuber mean yield, and small tuber mean yield. Variety of tuber size and intra-row spacing was also influenced by dry matter content and tuber specific gravity. The interaction effect of intra-row spacing and seed tuber size was significantly (P<0.05) influenced by the number of days to emergence. The day to flowering was also significantly (P<0.05) influenced by the interaction effect of variety and intra-row spacing. The maximum plant height (80.38 cm) was recorded with variety Gudenie with a tuber size of 66–80 g and planted at an intra-row spacing of 35 cm. The maximum (9.79) number of main stems was recorded in variety Jalenie with a tuber size of 81–95 g and planted at intra-row spacing of 40 cm. The maximum of total tuber yields (24.84 to/ha) was recorded from Jalenie variety with tuber size 66–80 g and planted at intra-row spacing of 25 cm. The maximum (10.18 t/ha) larger tuber was recorded with variety Gudenie with a tuber size of 66–80 g and planted at 25 cm. Variety Jalenie with tuber size of 66–80 g and planted at 25 cm produced the maximum (8.04 t/ha) medium-sized tubers. The maximum small tuber (8.59 t/ha) was recorded from both varieties with intra-row spacing of 20 cm and tuber size 81–95 g. Variety Gudenie planted at intra-row spacing of 40 cm gave higher (19.98%) dry matter content, and variety Gudenie with a tuber size of 66–80 g gave higher (20.61%) dry matter content. The higher (1.077) tuber specific gravity was obtained with variety Gudenie planted at intra-row spacing of 35 and 40 cm, and the higher (1.074) tuber specific gravity was registered with variety Gudenie with a tuber size of 66–80 g and/or 81–95 g and planted at intra-row spacing of 40 cm. The study needs in-depth investigation by repeating in multilocations with more seasons, varieties, processing quality, and other agronomic practices of the crop to reach a conclusive recommendation. The result of this research was presented to Jimma University since 2015.